2017
DOI: 10.18632/oncotarget.18484
|View full text |Cite
|
Sign up to set email alerts
|

Reversal effect of Jagged1 signaling inhibition on CCl4-induced hepatic fibrosis in rats

Abstract: The role of the Notch ligand Jagged1 in hepatic fibrosis remains to be elucidated. In the current study, we investigated the role of Jagged1 in the activation of hepatic stellate cells (HSCs) and development of hepatic fibrosis in rats. In vitro, Jagged1 in HSCs was downregulated and upregulated by Jagged1 siRNA and pcDNA3.1 Jagged1, respectively. The levels of epithelial-mesenchymal transition (EMT) markers and HSC activation markers were assessed using western blot analysis. The proliferation and migration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Our results indicate that both Ac‐HSC‐mediated JAG1‐NOTCH signaling and Ac‐HSC‐produced ECM play a pivotal role in directing HPC differentiation toward BECs, which could suppress the potential for HPCs as a source of HCs. A recent experiment has revealed the direct relationship between JAG1 and HSCs . In this article, the authors confirmed that JAG1 directly acts on the proliferation and epithelial–mesenchymal transition of HSCs in rat liver.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results indicate that both Ac‐HSC‐mediated JAG1‐NOTCH signaling and Ac‐HSC‐produced ECM play a pivotal role in directing HPC differentiation toward BECs, which could suppress the potential for HPCs as a source of HCs. A recent experiment has revealed the direct relationship between JAG1 and HSCs . In this article, the authors confirmed that JAG1 directly acts on the proliferation and epithelial–mesenchymal transition of HSCs in rat liver.…”
Section: Discussionsupporting
confidence: 74%
“…A recent experiment has revealed the direct relationship between JAG1 and HSCs. 46 In this article, the authors confirmed that JAG1 directly acts on the proliferation and epithelial-mesenchymal transition of HSCs in rat liver. Taken together with our observations, HSC-secreted JAG1 not only modulates HPC differentiation fate, but also acts on activated HSCs in their proliferation and maintenance.…”
Section: Discussionsupporting
confidence: 60%
“…TGF-β1 can promote the proliferation and activation of HSC-T25 cells by regulating the Notch signaling pathway ( Aimaiti et al, 2019 ). The Jagged1 gene was successfully knocked down by using rAAV1-Jagged1-shRNA in CCl 4 -induced liver fibrosis, resulting in alleviation of liver fibrosis ( Tang et al, 2017 ). In addition, knockout of the RBP-κB gene, which is considered a key transcription factor in the Notch pathway, can inhibit the proliferation and activation of HSCs to alleviate CCl 4 -induced liver fibrosis in mice ( He et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation and up-regulation of JAG1 inhibited and promoted, respectively, HSC activation. The migratory capacity of HSCs was markedly restrained by JAG1 siRNA ( 25 ). These reports coincide with our finding that JAG1 mediated adenomas progression by modulating cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%